Archaeal communities in natural and artificially restored mangrove sediments in Tieshan Bay, China - Wang, Zixiang; Zheng, Pengfei; Xing, Yongze; Mi, Tiezhu; Zhen, Yu (Frontiers in Marine Science, 2024)
Mangrove forests are crucial wetland ecosystems located in tropical and subtropical intertidal zones, but they have become extensively degraded. As a viable ecological restoration strategy, the cultivation of native mangrove vegetation in these degraded areas has gained considerable attention. Mangroves’ unique environmental conditions make them suitable habitats for diverse microbial communities, including Archaea - one of the main microbial communities in mangrove sediments - which plays a pivotal role in biogeochemical cycles. However, little is known about the dynamics of archaeal communities during mangrove restoration through phytoremediation. In this study, we investigated the physicochemical properties of sediment profiles from natural and artificially restored mangrove ecosystems in Tieshan Bay. We utilized quantitative polymerase chain reaction (qPCR) and 16S rRNA gene sequencing techniques to explore differences in abundance, community structure, and composition of archaeal communities between sediment profiles in natural and artificially restored mangrove ecosystems. We also examined correlations between archaeal communities and environmental factors. Our results revealed that Crenarchaeota, Thermoplasmatota, Asgardarchaeota, Nanoarchaeota, and Euryarchaeota were the predominant archaeal phyla, with significant variation in sediment composition observed for Crenarchaeota and Thermoplasmatota in different depths. We also found significant differences in archaeal abundance and community composition between natural and restored mangrove sediments. Furthermore, C/N ratio and pH emerged as primary drivers of archaeal communities in wet and dry season sediments, respectively. Additionally, the study revealed seasonal disparities in seasonal differences in the relative abundance of certain archaeal groups (such as Asgardarchaeota, Nanoarchaeota). Network analysis demonstrated stronger interconnections among archaeal communities in sediments from natural mangroves than from artificially restored ones. These findings enhance our knowledge of archaeal community succession patterns in mangrove restoration, as well as provide fresh perspectives for the sustainable management of mangrove ecosystems.